Influence of calcium silicate and sterilization on the natural suppressiveness and on the conduciveness of two soils to Rhizoctonia solani - Rodrigues, Fabrício de Ávila; Corrêa, Gilberto Fernandes; Kordorfer, Gaspar Henrique; Santos, Maria Amelia dos; Datnoff, Lawrence Elliot (Pesquisa Agropecuaria Brasileira, 1999)
The effect of calcium silicate slag and soil sterilization on the natural suppressiveness of a Typic Acrustox (clay Dark Red Latosol – LEa) and the natural conduciveness of an Oxic Haplustoll (TRe) to Rhizoctonia solani were studied under greenhouse conditions. The experimental design was a three-replicate completely randomized one, with 2 x 3 x 2 factorial combination of the following treatments: two soil kinds (LEa and TRe, collected at 0-20 cm layer); three treatments with and without soil sterilization, calcium silicate slag and nontreated control; and uninfested and infested with R. solani. Each soil material was infested previously with 800 mg of the inoculum per kg soil. Application of silicate was done mixing 0,63 g of this product with 1 kg each soil material and incubated for 30 days. The application of silicate increased the exchangeable Ca2+ and bases amount in both soils. The decrease in the aluminum saturation level from 70 to 19% and the increase in base saturation from 9 to 21% altered significantly the natural suppressiveness of LEa to R. solani. Application of silicate to the TRe had no effect on its conduciveness, for its natural eutrophic character, which is benefic to R. solani development. Sterilization by autoclavation did not influence disease development on bean by R. solani. This suggests that possibly other abiotic factors were responsible for either suppressiveness or conduciveness of these soils.